2012
DOI: 10.1186/1746-6148-8-215
|View full text |Cite
|
Sign up to set email alerts
|

Changes over time in craniocerebral morphology and syringomyelia in cavalier King Charles spaniels with Chiari-like malformation

Abstract: BackgroundChiari-like malformation (CM) and syringomyelia is a neurological disease complex with high prevalence in cavalier King Charles spaniels (CKCS). The natural progression of this disease with time has not been described. The objectives of this study were to i) determine if syringomyelia progresses with time ii) determine if features of craniocrebral morphology previously associated with CM are progressive (including caudal cranial fossa volume, caudal cranial fossa parenchymal volume, ventricular dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 29 publications
5
55
0
3
Order By: Relevance
“…Thus, in our cohort, approximately two‐thirds of asymptomatic dogs remained asymptomatic throughout the study period, despite the majority (>80%) having shown CCJ morphologic abnormalities on initial imaging. Previous studies in CKCS have shown a similar absence of correlation between clinical status at the time of imaging and the presence and severity of cerebellar herniation (presence and length), , cerebellar indentation, and foramen magnum height . One study, in fact, recently suggested that cerebellar indentation and impaction (ie, triangulation) should be considered a “normal” anatomic variation inherent to the CKCS breed, because of its high prevalence in asymptomatic CKCS.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, in our cohort, approximately two‐thirds of asymptomatic dogs remained asymptomatic throughout the study period, despite the majority (>80%) having shown CCJ morphologic abnormalities on initial imaging. Previous studies in CKCS have shown a similar absence of correlation between clinical status at the time of imaging and the presence and severity of cerebellar herniation (presence and length), , cerebellar indentation, and foramen magnum height . One study, in fact, recently suggested that cerebellar indentation and impaction (ie, triangulation) should be considered a “normal” anatomic variation inherent to the CKCS breed, because of its high prevalence in asymptomatic CKCS.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, the average tonsillar motion (CLM/CM-I with syrinx values given) was much greater and more variable in dogs (4.18 ± 2.63 mm according to Driver et al 16 ) than that in humans (current study 0.81 ± 0.47 mm; Bunck et al 5 1.0 ± 0.6 mm; Cousins and Haughton 11 0.61 ± 0.03 mm) despite similar or smaller degrees of herniation. 12,14,31 Whether increased cerebellar motion has a different effect on the canine system is unknown. Morphometric studies further suggest a probable difference between human and canine conditions.…”
mentioning
confidence: 99%
“…However, any dilatation of the central canal should be considered abnormal. Hence, the detection of smaller dilatations on both MR and CT is important as progressive central canal dilatation is a precursor of syrinx formation 1, 34. Furthermore, results of a previous study suggest that SW progresses with time in CKCS 34.…”
Section: Discussionmentioning
confidence: 98%